2021
DOI: 10.3389/fmicb.2021.650461
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Transposition of Multiple Insertion Sequences in Geobacillus kaustophilus HTA426

Abstract: Geobacillus kaustophilus HTA426 is a thermophilic bacterium whose genome harbors numerous insertion sequences (IS). This study was initially conducted to generate mutant genes for thermostable T7 RNA polymerase in G. kaustophilus; however, relevant experiments unexpectedly identified that the organism transposed multiple IS elements and produced derivative cells that expressed a silent gene via transposition. The transposed elements were diverse and included members of the IS4, IS701, IS1634, and ISLre2 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…In addition to the transposition of IS4, IS5, IS630, and IS200/IS605 into thyA through gamma-irradiation in D. radiodurans [49], another study recently reported that heat stress enhanced the transposition of multiple ISs via sigX-dependent stress response in Geobacillus kaustophilus [55]. In this case, the IS4, IS701, IS1634, and ISLre2 family members were transposed.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the transposition of IS4, IS5, IS630, and IS200/IS605 into thyA through gamma-irradiation in D. radiodurans [49], another study recently reported that heat stress enhanced the transposition of multiple ISs via sigX-dependent stress response in Geobacillus kaustophilus [55]. In this case, the IS4, IS701, IS1634, and ISLre2 family members were transposed.…”
Section: Discussionmentioning
confidence: 97%
“…Insertion sequence transposition has been detected under various environmental stressors, such as nutrient deprivation, temperature changes, metal ion exposure, and oxidative stress caused by UV irradiation, gamma irradiation, and H 2 O 2 treatment (Ohtsubo et al, 2005;Twiss et al, 2005;Kharat et al, 2006;Mijnendonckx et al, 2011;Suzuki et al, 2021). Interestingly, this active transposition of IS elements was found to vary in a species-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were cultured at 60°C using lysogeny broth under aerobic conditions. Genomic DNA was extracted from the cells using a cetyltrimethylammonium bromide-based method ( 3 ) and solubilized in 1 mL of a buffer that contained Tris-HCl at pH 8.0 (10 mM) and EDTA (1 mM). Genomic DNA was then purified from an aliquot of the resulting solution using NucleoSpin gDNA Clean-up kit (Takara Bio, Otsu, Japan).…”
Section: Announcementmentioning
confidence: 99%